2007
DOI: 10.1109/iembs.2007.4353059
|View full text |Cite
|
Sign up to set email alerts
|

Functional MR Imaging of the Cervical Spinal cord by Use of 20Hz Functional Electrical Stimulation to Median Nerve

Abstract: The functional MR imaging signal can be detected in the human cervical spinal cord with functional electrical stimulation. Investigating the FES response in the spinal cord using the spinal fMRI will be helpful for the further discussion on the diagnosis and functional recovery to spinal cord diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…BOLD-based imaging methods have gained an important role in such studies, though a second source of functional contrast, signal enhancement by extravascular water protons, has been also applied by several groups (Stroman et al 2002;Stroman 2005;Xie et al 2007). The present study was focused on BOLD fMRI since it has been widely used in brain fMRI studies such that the underlying mechanism of this contrast is better understood.…”
Section: Discussionmentioning
confidence: 98%
“…BOLD-based imaging methods have gained an important role in such studies, though a second source of functional contrast, signal enhancement by extravascular water protons, has been also applied by several groups (Stroman et al 2002;Stroman 2005;Xie et al 2007). The present study was focused on BOLD fMRI since it has been widely used in brain fMRI studies such that the underlying mechanism of this contrast is better understood.…”
Section: Discussionmentioning
confidence: 98%
“…Again in the rat, functional plastic changes at the spinal cord level following experimental spinal cord injury have been revealed by a recent fMRI study (20). After these piloting studies on the motor system, the somato-sensory system is also now successfully investigated in humans (44,91). These studies convincingly demonstrate that fMRI can be used to explore the function of the spinal cord in pain processing.…”
Section: Are "Classical" Pain-processing Regions Modulated When the Pmentioning
confidence: 88%
“…Spinal cord fMRI in the rat has been shown to anatomically distinguish signal changes related to motor, pain, and tactile activity (40,91). The study by Lilja et al (40) also showed a pharmacological modulation of the spinal cord signal in response to morphine, which could be reversed by naloxone.…”
Section: Are "Classical" Pain-processing Regions Modulated When the Pmentioning
confidence: 93%
“…9 Four authors noted that the expected location of functional activation of any particular dermatome or myotome was roughly one VB level above the intervertebral foramen that contains the nerve root supplying that dermatome or myotome. 24,28,33,34 Inducing Neural Activity in the Spinal Cord: Choice of a Stimulation Paradigm…”
Section: Localizing the Fmri Signal To An Anatomical Region Of The Spmentioning
confidence: 99%